Hypericin alleviates cerebral ischemia/reperfusion injury by modulating endoplasmic reticulum stress - Li, Tingting; Wang, Chao (Frontiers in Pharmacology, 2026)
IntroductionCerebral ischemia/reperfusion (I/R) injury remains a leading cause of neurological disability and is characterized by oxidative stress, calcium overload, inflammation, and endoplasmic reticulum (ER) stress following reperfusion. Hypericin, a bioactive naphthodianthrone derived from Hypericum perforatum, exhibits antioxidant and anti-apoptotic properties. This study investigated the neuroprotective effects and underlying mechanisms of hypericin in experimental cerebral I/R injury.MethodsMale Sprague-Dawley rats were subjected to middle cerebral artery occlusion (MCAO) and treated intraperitoneally with hypericin (5, 10, or 20 mg/kg) 30 minutes before reperfusion or nimodipine (10 mg/kg) as a positive control. Neurological severity scores (mNSS), grip strength, rotarod performance, infarct volume, and brain water content were evaluated 24 hours after reperfusion. In vitro, murine hippocampal HT22 cells underwent oxygen-glucose deprivation/reoxygenation (OGD/R) and were treated with hypericin (6.25-25 μg/mL). Cell viability (MTT assay), apoptosis (Annexin V/PI flow cytometry), and ER stress-related markers were assessed using qRT-PCR and Western blotting. In silico pharmacokinetic analysis was performed to evaluate blood -brain barrier permeability.ResultsHypericin significantly reduced cerebral infarct volume by approximately 40%, alleviated brain edema, and improved neurological and motor function compared with untreated I/R animals (p < 0.05). Histopathological and immunohistochemical analyses demonstrated preserved hippocampal structure and reduced caspase-3 activation. In OGD/R-injured HT22 cells, hypericin increased cell viability, reduced apoptotic rates from 30.3% to 10.3%, suppressed ER stress-associated markers (CHOP, GRP78, caspase-12), and normalized the Bax/Bcl-2 ratio. Pharmacokinetic predictions suggested moderate lipophilicity and physicochemical properties compatible with partial blood-brain barrier penetration, particularly under ischemia-induced barrier disruption.DiscussionThese findings demonstrate that hypericin confers significant neuroprotection against cerebral I/R injury by attenuating ER stress-mediated apoptosis and preserving neuronal integrity. Hypericin may represent a promising therapeutic candidate for ischemic stroke.